Oroxylum indicum– a medicinal plant of North East India: An overview of its nutritional, remedial, and prophylactic properties - D C Deka, Vimal Kumar, Chandan Prasad, Kamal Kumar, B J Gogoi, Lokendra Singh, R B Srivastava (Journal of Applied Pharmaceutical Science, 2013)
Oroxylum indicum (family: Bignoniaceae) or Broken bones tree, which is distributed throughout India and South East Asia. Oroxylum indicum is known by such regional names as Bhatghila, Tona, Bhut-vriksha, Shyonaka, and Hanyu pinyin. Over the past two decades, many reports have appeared in mainstream scientific journals describing its nutritional and medicinal properties. While much of this recent enthusiasm indeed appears to be justified, it is critical to separate rigorous scientific evidence from anecdote. The present review provides the complete information about literatures of Oroxylum indicum as botanical descriptions, vernacular names, biological activity of plant parts, ethanomedicinal uses and current status of research with scope of investigation of Oroxylum indicum for future research. The structures of twenty eight isolated compounds from different parts of Oroxylum indicum with IUPAC names, molecular formula, formula weight, melting points were also reported in this study.
Keywords: Oroxylum indicum, Flavonoids, Ant